Nonclinical Safety Assessment of Lipid Nanoparticle-and Emulsion-Based Self-Amplifying mRNA Vaccines in Rats. (January 2023) - Donahue, Douglas A.; Ballesteros, Cristina; Maruggi, Giulietta; Glover, Christiana; Ringenberg, Michael A.; Marquis, Miriam; Ben Abdeljelil, Nawel; Ashraf, Asma; Rodriguez, Luis-Alexander; Stokes, Alan H.
Vaccines containing mRNA with the capacity to self-amplify represent an alternative to the mRNA vaccines that came to prominence during the COVID-19 pandemic. To gain further insights on the safety profile of self-amplifying mRNA- (SAM-) vaccines, this preclinical toxicology study in rats evaluated the effect of (i) the type of delivery system (lipid nanoparticle [LNP] vs cationic nano-emulsion [CNE]); (ii) antigen-encoding sequence (rabies glycoprotein G vs SARS-CoV-2 Spike); and (iii) RNA amplification. Further analyses also evaluated gene expression in peripheral blood after vaccination, and the biodistribution of vaccine RNA. The SAM vaccines administered as two doses 2-weeks apart had acceptable safety profiles in rats, with respect to clinical signs, blood biochemistry, and macroscopic and microscopic pathology. A transient increase in ALT/AST ratio occurred only in female rats and in the absence of muscle and liver damage was dependent on RNA amplification and appeared related to the greater quantities of vaccine RNA in the muscle and livers of female rats vs male rats. The RNA and delivery-vehicle components, but not the nature of the antigen-coding sequence or the requirement for RNA amplification, affected aspects of the stimulation of innate-immune activity, which was consistent with the transient activation of type I and type II interferon signaling. The delivery vehicle, LNP, differed from CNE as vaccine RNA in CNE compositions appeared independently to stimulate innate-immune activity at 4 hours after vaccination. Our analysis supports further studies to assess whether these differences in innate-immune activity affect safety and efficacy of the SAM vaccine.